Twelve girls band and the representation of Chinese traditional musical instruments through virtual perspectives / Chen Pei Ying - Chen , Pei Ying (2017)
This study examines Twelve Girls Band and how Chinese traditional musical instruments were orchestrated to set a new tradition based on three selected popular Chinese folk songs. Biasness and much debate were put on among scholars; however, there is a lack of research with a more holistic approach that covers music analysis and virtual fieldwork. This research aims to fill the gap by examining into its orchestration, analysis of its music and then provide a thick description looking into Twelve Girls Band from a cultural and musical point of view, in order to bring to a more holistic view of its identity formation and how its music forms a new tradition. This research is in the area of ethnomusicology and popular music. Methodology includes virtual fieldwork and music analysis. Research outcome includes identification of a modelling concept of new orchestration that furnish new knowledge into the current debate of xinminyue or world music derived from music analysis and discussing Twelve Girls Band from a cultural perspective.